Theatre in Transition: Lars Elleström's Media Modalities and the Rise of "Video Theatre". - Timplalexi, Eleni (Critical Arts: A South-North Journal of Cultural & Media Studies)
During the COVID-19 pandemic, pre-recorded and recorded videos were extensively live-streamed or displayed on online platforms, usually as a substitute for the "real thing". Online theatre became an ambassador for theatre performance, remaining selectively oblivious to theatre's innovative digital paths of the past. The synergy between theatre and the digital was significantly reconfigured and its intermedial dimension escaped our collective attention, despite a silent process of media translation and appropriation (or even total transformation) unfolding. A comparative approach based on Lars Elleström's (2021, 2010) media modalities model suggests that a video recording of a theatre performance destined for the web differs from the actual theatre performance in terms of its material, spatiotemporal, sensorial and semiotic modalities to such an extent that it constitutes a different media type. An online video of a live theatre performance emerges as an intermedial phenomenon with a strong transmedial dynamic and is found to belong to the sphere of media transformation. This new media type of "video theatre/drama" may acquire artistic value per se, when it develops self-awareness, addresses aesthetics and establishes its own poetics.